Aqueous CO2 Reduction on Si Photocathodes Functionalized by Cobalt Molecular Catalysts/Carbon Nanotubes. (23rd March 2022) - Wen, Zhibing; Xu, Suxian; Zhu, Yong; Liu, Guoquan; Gao, Hua; Sun, Licheng; Li, Fei
Abstract: Photoelectrochemical reduction of CO2 is a promising approach for renewable fuel production. We herein report a novel strategy for preparation of hybrid photocathodes by immobilizing molecular cobalt catalysts on TiO2 ‐protected n + ‐p Si electrodes (Si| TiO2 ) coated with multiwalled carbon nanotubes (CNTs) by π–π stacking. Upon loading a composite of Co II (BrqPy) (BrqPy =4′, 4′′‐bis(4‐bromophenyl)‐2, 2′ : 6′, 2′′ : 6′′, 2′′′‐quaterpyridine) catalyst and CNT on Si| TiO2, a stable 1‐Sun photocurrent density of −1.5 mA cm −2 was sustained over 2 h in a neutral aqueous solution with unity Faradaic efficiency and selectivity for CO production at a bias of zero overpotential (−0.11 V vs. RHE), associated with a turnover frequency (TOFCO ) of 2.7 s −1 . Extending the photoelectrocatalysis to 10 h, a remarkable turnover number (TONCO ) of 57000 was obtained. The high performance shown here is substantially improved from the previously reported photocathodes relying on covalently anchored catalysts. Abstract : A hybrid photocathode prepared by attaching a molecular cobalt catalyst on a n + ‐p Si film coated with multiwalled carbon nanotubes (CNTs) exhibits 100 % selectivity and 100 % Faradaic efficiency towards CO2 ‐to‐CO conversion in aqueous media under simulated sunlight irradiation. The high performance benefits from CNTs as both a support platform for highly dispersed molecular active sites and an efficient mediator for charge transfer.